Relationship of Anxiety, Stress & Depression with Self Esteem Among Undergraduate Medical Students - Naeem Amjad, Samia Sarwar, Muhammad Amin Khan, Farrukh Sarrfraz, Rizwan Saeed, Qurratulain Mehfooz, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: According to a recent study conducted by the Anxiety and depression Association of America seven out of 10 Joined together States adults claim to encounter push or uneasiness at least at a moderate level on every day premise. Whereas stress is an inevitable portion of life, it is exceptionally present and getting to be more prevalent among college students. In expansion to anxiety and stress, discouragement can also impact college life to such a degree that in-depth research is necessary in arrange to assist future students. Within the USA, nearly 10% of college students have been analyzed with, or treated for, depression over the past 12 months. However, only almost half of the individuals in America enduring from a diagnosed case of sadness are treated for the disorder. Past research on Anxiety, depression and self-esteem highlights that low self-esteem is related to higher levels of uneasiness, misery and stress. Be that as it may, this correlation has not been clearly illustrated in Pakistani young people especially medical students. Objective: To investigate the relationship of Anxiety, Stress & Depression with Self Esteem among undergraduate medical students Material and Methods Study design: Quantitative cross sectional Settings: Shahida Islam Medical College Lodhran Duration: Four months i.e. 1st January 2022 to 30th April 2022 Data Collection procedure: Cross sectional was conducted on 250 medical students. Data was collected by validated questionnaire. The depression, anxiety and stress scale (DASS) was used for the calculation of stress, anxiety and depression and Rosenberg self-esteem scale used to calculate the self-esteem. Data was collected after informed consent taken from students. The students who have been suffering any kind of diseases excluded from study. Data was analyzed using SPSS version 22 for results. Results: The total number of medical students was 250 in which 105 were males and 145 females. Students selected from all levels of MBBS 42% males and 58% females. In table 2 regarding depression 60.4% students fall in normal, 23.6% fall in mild, 14% fall in moderate and 2% in severe category. As far Anxiety is concerned 52% students fall in normal, 22% fall in mild, 19.2% fall in moderate and 6.8% in severe category and for stress 56.8% students fall in normal, 26% fall in mild, 17.2% fall in moderate and 0% in severe category. Conclusion: The move to adulthood represents a high-risk period for the onset of depression generally young individuals who enter tertiary education may face modern social and mental challenges that will increase their chance of enduring sadness, uneasiness and stress. The high rates of depression, anxiety and stress among students have major suggestions. Not as it were will mental morbidity have adverse impacts on the student’s educational attainment and quality of life, but family life and institutional life may be disrupted. Change of these, as well as arrangement of mental wellbeing facilities and mindfulness to medical students may make strides the self-esteem, stress administration as well as mental trouble among medical students. Keywords: Anxiety, Depression, Stress, Self Esteem, Mental health, Students.